Mechanisms of Damage to the Gastric Mucosa in Mixed Injuries (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article provides data on damage to the stomach in mixed injuries. Mixed injuries can lead to rupture of intra-abdominal structures, which causes bleeding and release of stomach, intestinal or bladder contents into the abdominal cavity. This can lead to peritonitis and other serious complications. Bleeding may be slight or heavy, depending on the extent of the damage. More severe injuries may result in shock, acidosis, and coagulopathy. In these cases, surgery is required.Late complications of abdominal trauma may include hematoma rupture, intra-abdominal abscess, intestinal obstruction or ileus, bile leak and/or biloma, and abdominal compartment syndrome. Complications of treatment may also include abscess, intestinal obstruction, abdominal compartment syndrome, and late incisional hernia. Understanding the mechanisms of damage to the gastric mucosa during mixed injuries is crucial for timely diagnosis and treatment, as well as for the prevention of complications.